Implementasi Kebijakan Posyandu untuk Meningkatkan Partisipasi Ibu dan Balita di Kecamatan Kuta - Astawa, Ida Bagus; Widnyani, Ida Ayu Sri; Dewi, Inyoman Diah Utari (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
This study aims to examine the implementation of the toddler Posyandu (Integrated Health Service Post) policy in increasing the participation of mothers and toddlers in Kuta Selatan District, Badung Regency, Bali. The research addresses the problem of low attendance in Posyandu activities despite structured scheduling and government efforts to improve maternal and child health. Using a qualitative descriptive approach, data were collected through in-depth interviews, direct observation, and documentation. Informants included Posyandu cadres, local health workers, and participating mothers selected purposively. The analysis refers to Edward III’s policy implementation theory, focusing on communication, resources, disposition, and bureaucratic structure. The findings reveal that although the policy has been generally implemented, several challenges remain, such as limited parental awareness, conflicting schedules, and inconsistent service quality. Coordination between health workers and cadres is also not optimal. Nevertheless, efforts like home visits, health education, and local media campaigns have been carried out to increase awareness and participation. The study recommends strengthening intersectoral coordination, enhancing the capacity of Posyandu cadres, and conducting continuous socialization efforts. These steps are crucial to ensure that mothers and toddlers receive timely and adequate health services through Posyandu activities.